Observations on the growth of postlarvae of Macrohrachium rosenhergii in polythene sheet covered earthen nursery ponds during winter - Pillai, Bindu R; Tripathy, A P; Rao, K J (Indian Journal of Fisheries, 2011)
Growth of postlarvae of Macrohrachium rosenhergii reared in polythene covered earthen nursery ponds (polyhouse) was evaluated during winter. The polyhouse ponds along with two control ponds (60 m^ each) were stocked with postlarvae (0.013Â±0.004 g) at 40,000/ha stocking density. The prawns were fed with a formulated feed (35 % crude protein) at the rate of 10 % of the biomass and were reared for 100 days. The percentage survival varied widely (24-82) in different ponds. Average daily growth in polyhouse nursery ponds was found to be 83.72 % higher than the control ponds.